Late Gadolinium Enhancement in Cardiac Magnetic Resonance Imaging Is Associated with High Renal Resistive Index in Patients with Systemic Sclerosis - Rosario Cianci; Antonietta Gigante; Maria Ludovica Gasperini; Biagio Barbano; Nicola Galea; Edoardo Rosato (Karger Publishers, 2020)
Introduction: Systemic sclerosis (SSc) is a chronic autoimmune disease characterized by microvascular damage and fibrosis of the skin and internal organs. The major complications are lung fibrosis, pulmonary artery hypertension, scleroderma renal crisis, and cardiac involvement. Objective: The aim of this study was to assess renal and cardiac involvement in asymptomatic SSc patients using renal Doppler ultrasound (RDU) and cardiac magnetic resonance (CMR). Materials and Methods: We enrolled 26 consecutive SSc patients (21 female) according to 2013 ACR/EULAR criteria. Biochemical analysis, clinical evaluation, RDU with intrarenal hemodynamic parameters (renal resistive index [RRI], pulsatility index [PI], systolic/diastolic [S/D] ratio), and CMR with late gadolinium enhancement (LGE) were investigated at the time of enrollment. Results: The median PI value was significantly (p = 0.007) higher in SSc patients with LGE than in SSc patients without LGE (1.37 [1.28-1.58] vs. 1.12 [1.06-1.26]). The median RRI value was significantly (p = 0.002) higher in SSc patients with LGE than in SSc patients without LGE (0.68 [0.65-0.73] vs. 0.64 [0.63-0.65]). The median S/D ratio was significantly (p = 0.02) higher in SSc patients with LGE than in SSc patients without LGE (3.12 [2.83-3.76] vs. 2.78 [2.64-2.84]). Conclusions: Our study, although performed on a small SSc population, showed RRI and LGE as markers of vascular and fibrotic damage. Early detection of cardiorenal involvement in SSc patients without symptoms is important to avoid further complications.